1964
DOI: 10.1139/v64-141
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Absorption in Copper(ii) Stearate

Abstract: The magnetic moment of copper in copper(I1) acetate is known to decrease as the temperature is lowered (1, 2). This anonlalous effect has been explained by assuming that the copper ions are arranged in isolated pairs which interact strongly through exchange forces (3). X-Ray studies, supporting this explanation, have shown that copper(I1) acetate monohydrate exists as a binuclear molecule Cu2(CH3C02) 4.2H20 in which the copper ions are situated close together (4). By analogy, a similar structure has been sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…EXAFS studies revealed that the metal basal plane remained virtually unchanged both in the lamellar crystal and mesomorphic phase [169]. However, variable temperature infrared analyses showed an increase in the stretching frequencies of the CH 2 group as a result of disordering of the alkyl chains in the mesophase [167] in agreement with dilatometric and 1 H-NMR studies [170]. These results confirmed that the mesophase was composed of partially disordered alkyl chains anchored to unperturbed metal basal plane aggregates.…”
Section: Divalent Carboxylatessupporting
confidence: 52%
“…EXAFS studies revealed that the metal basal plane remained virtually unchanged both in the lamellar crystal and mesomorphic phase [169]. However, variable temperature infrared analyses showed an increase in the stretching frequencies of the CH 2 group as a result of disordering of the alkyl chains in the mesophase [167] in agreement with dilatometric and 1 H-NMR studies [170]. These results confirmed that the mesophase was composed of partially disordered alkyl chains anchored to unperturbed metal basal plane aggregates.…”
Section: Divalent Carboxylatessupporting
confidence: 52%
“…Examples for the structures of binuclear complexes are given in Scheme .
1 Examples for Binuclear Complexes a a Left to right: dinuclear azopalladium(II) complex, alkoxy-substituted bis(1,5-diphenyl-1,3,5-pentanetrionato)dicopper(II) complex, and dinuclear tetraalkanoate−copper(II) complex
2 Synthetic Route to Ring- and N-Substituted Salicylaldimine Complexes 3
…”
Section: Introductionmentioning
confidence: 99%
“… a Left to right: dinuclear azopalladium(II) complex, alkoxy-substituted bis(1,5-diphenyl-1,3,5-pentanetrionato)dicopper(II) complex, and dinuclear tetraalkanoate−copper(II) complex …”
Section: Introductionmentioning
confidence: 99%